Progress toward UNAIDS 90-90-90 targets: A respondent-driven survey among female sex workers in Kampala, Uganda - Doshi, Reena H.; Sande, Enos; Ogwal, Moses; Kiyingi, Herbert; McIntyre, Anne; Kusiima, Joy; Musinguzi, Geofrey; Serwadda, David; Hladik, Wolfgang (PLoS ONEv, 2018)
We investigated progress towards UNAIDS 90-90-90 targets among female sex workers in Kampala, Uganda, who bear a disproportionate burden of HIV. Methods Between April and December 2012, 1,487 female sex workers, defined as women, 15±49 years, residing in greater Kampala, and selling sex for money in the last 6 months, were recruited using respondent-driven sampling. Venous blood was collected for HIV and viral load testing [viral load suppression (VLS) defined as <1,000 copies/mL]. We collected data using audio computer-assisted self-interviews and calculated weighted population-level estimates. Results The median age was 27 years (interquartile range: 23 to 32). HIV seroprevalence was 31.4% (95% confidence interval [CI]: 29.0, 33.7%). Among all female sex workers who tested HIV-positive in the survey (population-level targets), 45.5% (95% CI: 40.1, 51.0) had knowledge of their serostatus (population-level target: 90%), 37.8% (95% CI: 32.2, 42.8) self-reported to be on ART (population-level target: 81%), and 35.2% (95% CI: 20.7, 30.4) were virally suppressed (population-level target: 73%). Conclusions HIV prevalence among Kampala female sex workers is high, whereas serostatus knowledge and VLS are far below UNAIDS targets. Kampala female sex workers are in need of intensified and targeted HIV prevention and control efforts.
Keywords: UNAIDS 90-90-90 targets; Female sex workers; Uganda